A Novel Platform Featuring Nanomagnetic Ligand Fishing Based on Fixed-Orientation Immobilized Magnetic Beads for Screening Potential Cyclooxygenase-2 Inhibitors from Panax notoginseng Leaves - Fan Zhang; Fan Sun; Lequan Yu; Fei Li; Lixia Liu; Xiaoyan Cao; Yi Zhang; Lijie Wu (Molecules)
A novel screening platform based on an Fe3O4@C@PDA-Ni2+@COX-2 ligand fishing combination with high-performance liquid chromatography–mass spectrometry was first designed, synthesized, and employed to screen and identify COX-2 inhibitors from Panax notoginseng leaves. The obtained magnetic nanoparticles exhibit outstanding preconcentration ability that allows for controlling the enzyme orientation to avoid enzyme active site blocking, conformational changes, or denaturing during immobilization. The as-prepared Fe3O4@C@PDA-Ni2+@COX-2 composite was carefully characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier-transform infrared spectrometry (FT-IR), Xray powder diffraction (XRD), thermal gravimetric analyzer (TGA), vibrating sample magnetometer (VSM), and Zeta potential analysis. The analytical parameters influencing the magnetic solid-phase fishing efficiency were optimized by univariate and multivariate methods (Box–Behnken design) by testing a positive control and celecoxib with active and inactive COX-2. Under the optimized ligand fishing conditions, twelve potential COX-2 inhibitors were screened and characterized in Panax notoginseng leaves. The results indicate that the proposed method provides a simple, feasible, selective, and effective platform for the efficient screening and identification of active compounds from Chinese herbal medicine. It has guiding significance for the synthesis and development of novel anti-inflammatory drugs, and provides a reference for the efficient discovery of anti-inflammatory drugs or lead compounds from the complex system of Chinese herbal medicine.